Oral Allergy Syndrome in a Child Provoked by Royal Jelly - Fantini Paola; Delle Donne Pantalea; Calogiuri Gianfranco; Ferrannini Antonio; Vacca Angelo; Nettis Eustachio; Di Leo Elisabetta (Case Reports in Medicine)
Royal jelly has been demonstrated to have several physiological activities. However, in the literature, different reactions induced by royal jelly are reported. We describe a case of seven-year-old child that was referred to our observation for two episodes of oral allergy syndrome (OAS) that appeared ten minutes after ingestion of royal jelly. Skin prick test with standard panel of inhalant and food allergens, a prick-to-prick test using the royal jelly’s extract responsible for patient’s reactions, and royal jelly patch test with extemporaneous preparation were performed. The specific IgE by ImmunoCAP System method versus Hymenoptera venom, inhalant allergens, food allergens, and lipid transfer proteins was dosed. According to the positive reactions to royal jelly both by prick-by-prick test and by a first reading patch test, royal jelly immediate hypersensitivity was diagnosed. According to the positive response for almond in both in vivo and in vitro tests we can think of the royal jelly contamination with almond pollen as possible cause of patient’s reaction. Moreover, from the results of specific IgE titers versus Compositae pollens, we have argued the possibility that this case of royal jelly allergy could be explained also by the mechanism of cross-reaction with Compositae pollens.